Hypocalcification and hypoplasia in primary teeth of pre-school children from different ethnic groups in South Africa - Hargreaves, J. A.; Cleaton-Jones, P. E.; Roberts, G. J.; Et al (My University, 1989)
A study was completed in 1985/86 which examined the dental health of pre-school children from different ethnic groups and communities in South Africa: rural black, urban black, urban colored, urban Indian, and urban white. Enamel defects were recorded in primary teeth by use of the HHI, an index developed to measure hypocalcification and hypoplasia of enamel. The findings showed that colored children had the greatest number of enamel defects. The teeth most commonly affected were the maxillary anterior teeth and mandibular molar teeth. It is suggested that further epidemiological studies utilizing the HHI should be undertaken in pre-school children, especially from developing countries, to gain more information on the causes of enamel defects in the primary dentition and the possible use of such findings to predict nutritional health of individuals.
Keywords: Dental Enamel Hypoplasia; Tooth Abnormalities; Tooth, Deciduous